(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The concept of custom is also present in psychology, and it means an action that is formed under the influence of certain circumstances, is strengthened in a person’s character, and is later performed involuntarily. Tradition covers a wide range as a phenomenon characteristic of all spheres of social life, work, and culture